ICTs for the Cognitive and Metacognitive abilities of the students with Specific Learning Disorder in Mathematics - Chatzivasileiou, Panagiota; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
This article is a literature review that analyses the cognitive and metacognitive abilities of the students with Specific Learning Disorder in Mathematics (SLDM). It aims to present the cognitive and metacognitive deficits of these students along with the ways and methods that can improve the corresponding cognitive and metacognitive abilities and analyze the role of the metacognitve knowledge in mathematics education. It also aims to present ICT tools that are used worldwide in order to asses and improve these abilities. These tools are designed for the assessment or the training of either the cognitive or the metacognitive abilities of the students with SLDM and include mobile and computer based applications, applications that use artificial intelligence and educational robotics.